Cryptogenic embolic stroke and cancer - Carneado-Ruiz, Joaquin (Frontiers in Neurology, 2025)
Oncologic and cerebrovascular diseases are among the diseases with the highest incidence rate and are leading causes of disability and mortality. The relationship between cancer and cerebrovascular disease has been studied for decades, yet it remains a challenge. Stroke, in relation to oncologic diseases, has particularities in its diagnosis and treatment. Cancer is an established risk factor for ischemic stroke. The highest risk of stroke occurs within the first 6 months after a cancer diagnosis and in patients with metastases. Between 2 and 10% of patients initially diagnosed with cryptogenic stroke are subsequently diagnosed with cancer within 1 year. The mechanism underlying cryptogenic ischemic stroke associated with oncologic disease is acquired hypercoagulability, which is the most frequent mechanism underlying stroke in patients with cancer. Sometimes, cancer presents itself as non-bacterial thrombotic endocarditis (NBTE) with cerebral infarction. Strokes are usually more severe, and their clinical presentation can be focal or multifocal. D-dimer levels are significantly elevated in patients with cancer-associated stroke. Magnetic resonance imaging (MRI) usually shows embolic lesions across several arterial territories, including both carotid territories and the vertebrobasilar territory. Patients with cancer-associated stroke face a higher risk of recurrence, recurrent thromboembolism, early neurological deterioration, and mortality. Patients with both stroke and cancer should be considered for thrombolysis (recombinant tissue plasminogen activator (rTPA) or tenecteplase) and endovascular treatment. Low-molecular-weight heparin is usually used empirically when a hypercoagulable state is suspected, and few studies have supported the use of direct oral anticoagulants as an option with similar efficacy. The objective of this review was to synthesize all relevant information available to date on neoplasia as a cause of cryptogenic embolic stroke and to provide useful insights for everyday clinical practice.